Influence of boron sprays on the boron and calcium content, fruit physiology disorder and storage of the citrus - LIANG He; SHI Wei-yong; MA Guo-rui; YANG Yu-ai (浙江大学学报. 农业与生命科学版, 2000)
0.2% B (H3BO4) solution was sprayed to citrus tree growing on a low B, Ca soil during the bloom and the effects of boron on the content of B and Ca, the fruit physiology disorder and storage of different citrus genotypes was studied. The results showed that the B, Ca content in the leaves, peel and pulp was positively related to B treatment in early stage of fruit development, fruit expand period and fruit mature period; the Ca/B ratio in the leaves and in the fruits decreased significantly during early stage of fruit development and fruit expand period. The B treatment decreased the physiology disorders of the fruit in the fruit development and the rotten fruit rate during storage as well.